Spontaneous stone expulsion in patients with history of urolithiasis. Issue 2 (May 2023) - Golomb, Dor; Shemesh, Amit; Goldberg, Hanan; Shalom, Ben; Hen, Eyal; Barkai, Eyal; Atamna, Fahed; Abu Nijmeh, Haitham; Cooper, Amir; Raz, Orit
Objectives: To examine differences in the presentation, management, and outcomes of patients admitted to the emergency department (ED) with ureteral stones, with prior history of urolithiasis compared to patients with a first stone event. Patients and Methods: Retrospective analysis of patients who visited the ED that were found to have a ureteral stone on CT. Patients were stratified into two groups: without history of urolithiasis (Group 1) and with history of urolithiasis (Group 2). Results: Between 2018 and 2020, 778 patients were admitted with ureteral stones. Patients in group 1 presented with a higher mean serum creatinine ( p  = 0.02), larger mean stone size ( p  < 0.0001), and a higher proportion of proximal ureteral stones ( p  < 0.0001) than patients in group 2. The 30 day readmission rate was significantly higher in group 1 ( p  = 0.02). Spontaneous stone expulsion was higher in group 2 ( p  < 0.0001), whereas the need for endourological procedures was higher in group 1 ( p  < 0.0001). On multivariable analysis serum creatinine (OR 0.264, 95% CI 0.091–0.769, p  = 0.01) and stone size (OR 0.623, 95% CI 0.503–0.771, p  < 0.0001) were associated with a lower spontaneous stone expulsion rate. History of prior endourological procedures (OR 0.225, OR 0.066–0.765, p  = 0.01) was associated with a higher spontaneous stone expulsion rate. Conclusions: Our data suggests that patients who are first time stone formers present with larger and more proximal ureteral stones, with a lower likelihood of spontaneous stone expulsion and a subsequent need for surgical intervention. Previous stone surgery and not previous stone expulsion was found to be a predictor for spontaneous stone passage.